2015
DOI: 10.1080/19443994.2015.1054887
|View full text |Cite
|
Sign up to set email alerts
|

Comparative removal of Magenta MB from aqueous solution by homogeneous and heterogeneous photo-Fenton processes

Abstract: A B S T R A C TWastewaters originating from dyes production and application industries pose a major threat to surrounding ecosystems because of their toxicity and potentially carcinogenic nature. In this study, the removal of a reactive azo dye called Magenta MB (MMB) was done by photo-Fenton process using heterogeneous Fe 3 O 4 catalyst and homogeneous FeSO 4 catalyst. The effect of different system variables namely catalyst concentration, H 2 O 2 dosage, pH, and initial concentration of the dye were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…It is shown that the demand for electric energy to treat real wastewaters is much higher in comparison to single compounds, as is the amount of reagents required to degrade the organic carbon. These results were in agreement with the work of Xavier et al [47], who observed that the application of an excess of Fe 2+ increased the scavenging reactions and decreased the efficiency of the photo-Fenton process in the degradation of Magenta MB. Parallel to the kinetic rate, the energy consumption was determined to evaluate the feasibility of the reactor.…”
Section: Effect Of Fe 2+ Concentrationsupporting
confidence: 93%
“…It is shown that the demand for electric energy to treat real wastewaters is much higher in comparison to single compounds, as is the amount of reagents required to degrade the organic carbon. These results were in agreement with the work of Xavier et al [47], who observed that the application of an excess of Fe 2+ increased the scavenging reactions and decreased the efficiency of the photo-Fenton process in the degradation of Magenta MB. Parallel to the kinetic rate, the energy consumption was determined to evaluate the feasibility of the reactor.…”
Section: Effect Of Fe 2+ Concentrationsupporting
confidence: 93%
“…Recently, electrochemical sludge was used effectively to activate PMS for the removal of nanomaterials from water. [114] In addition to the classic Fenton process, electro-Fenton, [115] sono-Fenton, [116] and photo-Fenton [117] technologies have gained prominence in recent decades. The classic Fenton process which uses iron in soluble form suffers from various limitations including the requirement of acidic pH 3, generation of iron sludge which further needs treatment to safe disposal.…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%
“…To overcome these disadvantages, advanced oxidation processes (AOPs) should be preferentially used. Among these AOPs are, photocatalysis, [10][11][12] electrocatalysis, 13 photo-electrocatalysis, 14 electro-Fenton, [15][16][17][18] Fenton, 19,20 peroxicoagulation, 21,22 photo-Fenton, 23 sono-Fenton, 24 sonochemical methods, 25 hydrodynamic cavitation, 26 zero valent metals based AOPs, 27,28 and oxidation processes based on the use of radicals (SO 4 −• , OH • ). 29,30 However, the oxidation by the radicals…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages, advanced oxidation processes (AOPs) should be preferentially used. Among these AOPs are, photocatalysis, electrocatalysis, photo‐electrocatalysis, electro‐Fenton, Fenton, peroxicoagulation, photo‐Fenton, sono‐Fenton, sonochemical methods, hydrodynamic cavitation, zero valent metals based AOPs, and oxidation processes based on the use of radicals (SO 4 −• , OH • ) . However, the oxidation by the radicals of sulfate SO 4 −• attracted a lot of attention because of the high oxidation potential that is expected at 2.01 V compared to others radicals .…”
Section: Introductionmentioning
confidence: 99%